The status of Australian nurse practitioners: the second national census - Middleton, S.; Gardner, A.; Gardner, G.; Della, Phillip (CSIRO Publishing, 2011)
Objectives: To profile nurse practitioners and their practice in Australia in 2009 and to compare with resultsof a similar census conducted in 2007.Methods: A questionnaire was distributed by the nursing registering authority in each state except in SouthAustralia where recruitment was conducted via the Australian College of Nurse Practitioners website.Results: 293 nurse practitioners responded (response rate 76.3%). The majority were female (n=229,81.2%); mean age was 47.3 years (SD=8.1). As in 2007, emergency nurse practitioners represented thelargest clinical field of practice (n=63, 30.3%). A majority of nurse practitioners practiced in a metropolitanarea (n=133, 64.3%); a decrease from 2007. Consistent with 2007, only 71.5% (n=208) of respondents wereemployed as a nurse practitioner and 22.8% were awaiting approval for some or all of their clinicalprotocols (n=46). Demographic data, allocations of tasks, and patterns of practice remained consistent with2007 results. The majority of participants employed as nurse practitioner reported ‘no Medicare providernumber’ (n=182/200, 91.0%), ‘no authority to prescribe medications through the Pharmaceutical BenefitsScheme’ (n=182/203, 89.6%) and ‘lack of organisational support’ (n=105, 52.2%) as ‘limiting’ or ‘extremelylimiting’ to their practice.Conclusions: That only 72% of participants were working as nurse practitioners, despite being authorised todo so, and that this figure had not decreased within the last two years indicated less than satisfactoryuptake of this role. Whilst barriers constraining nurse practitioner practice reduced, these, nonetheless,remained unacceptably high. Adequate professional and political support is clearly necessary to ensure theefficacy and sustainability of this clinical role.